1999
DOI: 10.1108/02630809910302935
|View full text |Cite
|
Sign up to set email alerts
|

Dissatisfaction with stock condition surveys in social housing

Abstract: This paper arises from findings which emerged during the preparation of the Good Practice Guide to Maintenance Cost Forecasting. This Guide was commissioned by the Housing Corporation to assist Registered Social Landlords forecast the future maintenance costs of their stocks. It became apparent during the work that client experiences of stock condition surveys had been far from satisfactory. The surveys had often been carried out by professional surveyors and yet many had fundamental weaknesses in their specif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2001
2001
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 1 publication
0
8
0
Order By: Relevance
“…The defects are registered during a condition survey or condition assessment. In for instance the UK, client experiences of stock condition surveys has been far from satisfactory (Chapman, 1999). The practice of condition assessment by building inspectors yields variable results due to subjective perceptions of inspectors.…”
Section: Introductionmentioning
confidence: 99%
“…The defects are registered during a condition survey or condition assessment. In for instance the UK, client experiences of stock condition surveys has been far from satisfactory (Chapman, 1999). The practice of condition assessment by building inspectors yields variable results due to subjective perceptions of inspectors.…”
Section: Introductionmentioning
confidence: 99%
“…In developed countries, such as the UK, it is a requirement of HEFCE that universities carry out building condition surveys and that periodic strategic maintenance reports are presented to the university management. However, the effectiveness and shortcomings of the condition survey have already been seriously questioned (O'Dell 1996;Chapman 1998;Umeadi and Jones 2003).…”
Section: Condition Surveymentioning
confidence: 98%
“…Earlier research by Chapman (1999) revealed that a large number of housing associations in England had found stock condition surveys to be completely unsatisfactory. This was often caused by poor specification of organisations' initial requirements or poor survey procedures.…”
Section: Role Of Stock Condition Surveysmentioning
confidence: 98%
“…Meanwhile, since the work of Chapman and Beck (1998) and Chapman (1999), much research has been undertaken into the concept of surveyor variability. Procedures and processes to improve the accuracy of information from stock condition surveys have also been developed.…”
Section: Role Of Stock Condition Surveysmentioning
confidence: 99%